Correlation between Family Support and Health Professional Education on Tuberculosis Patient Compliance at Public Health Centers Tasikmalaya - Anshar, Doni; Fadhilla, Genialita; Wulansari, Wulansari (Fakultas Farmasi Universitas Andalas, 2023)
Tuberculosis prevalence in Indonesia is still high, as 824,000 people are infected with Tuberculosis (Indonesia Basic Health Research 2022). This shows that Tuberculosis is still difficult to control due to various factors, including patient compliance. Patient compliance can be influenced by family support and health professional’s education about Tuberculosis therapy, which plays an important role in increasing knowledge of correct therapy for patients and families. This study examines the influence of family support and health professional education on tuberculosis patient compliance. This is a descriptive study with the cross-sectional method. Data was collected from 52 Tuberculosis patients who met the inclusion criteria using a questionnaire. The result shows that family support and health professional education had very good scores (84.6% and 46.2%) on Tuberculosis patients. This affects patient compliance is very good (82.7%). Based on correlation results, it shows that there is a direct influence of family support (p-value<0.05). At the same time, there is an indirect influence of health professional education on patient compliance (p-value>0.05). This shows that family support has a greater direct influence than health professional education on tuberculosis patients’ compliance. However, health professionals still play an important role because the patient's family also receives education from health professionals.